The impact of time and power allocation on the performance of the three-node decode and-forward relay channel - Khairol Fauzi, Muhammad Zarol Fitri; Elsheikh, Elsheikh Mohamed Ahmed (Institute of Electrical and Electronics Engineers Inc., 2017)
Relying has in use for decades to tackle some of the challenges of wireless communication such as extending transmitting distance, transmitting over rough terrains. Relaying also achieve diversity which was proposed recently as an effective means to combat channel fading. In this work, effect of time and power allocation on relay performance is studied. The channel considered is the three-node channel with half-duplex constraint on the relay. The relaying technique assumed is decode-and-forward. Mutual information is used as the criteria to measure channel performance whereas noise is assumed to be the primary channel impairment. After deriving suitable formula for the mutual information as a function of time and power allocation, numerical results are obtained. Results have shown that the importance of relaying is more apparent when more resources are allocated to the relay. It was also shown that quality of the source to destination link has direct impact on the decision to relay or not to relay. Relatively good source to destination channel makes relaying less useful. The opposite is true for the other two links, namely the source to relay channel and the relay to destination channel. When these two channels are good, relaying becomes advantageous.